Analisis Pengelolaan Barang Milik Daerah (BMD) pada Pemerintah Daerah Kabupaten Pandeglang - Wardani, Ni Made Sri; Lestari, Utami Puji; Nugroho, Herbirowo (Politeknik Negeri Jember, 2025)
This research was conducted to determine the implementation of the Minister of Home Affairs Regulation Number 19 of 2016 concerning the management of regional property, the inhibiting factors, and recommendations for the management of regional property in the Government of Pandeglang Regency. This research is a qualitative descriptive study. This research uses data sources in the form of primary and secondary data. The data collection techniques in this research are interviews, observations (primary data), and documentation. The data collection method involves conducting interviews with the Sub-Field of Regional Property Empowerment (BMD) of the BPKD and the Head of the Regional Accounting Field of Pandeglang Regency regarding the management of BMD. Interviews are conducted both offline and online. The research results show that the implementation of the Minister of Home Affairs Regulation Number 19 of 2016 on the management of regional property in the Pandeglang Regency Government is in accordance with the regulations. However, there are still discrepancies in the security and maintenance activities, destruction and disposal activities, and in the BMD administration activities.